SISTEM AKUNTANSI WAKAF SEBAGAI BENTUK PERTANGGUNGJAWABAN HARTA WAKAF KE PUBLIK - Windu Mulyasari (FEB Universitas Sultan Ageng Tirtayasa, 2017)
Abstract Accountability needs for Nazhir on waqf property becomes an important question. Nazhir as waqf management agency has responsibility to manage waqf property. However, in Indonesia, the law and economics of accountability waqf property is still a matter of debate. Management information system needs to be done as a form of accountability reports waqf property management. One of the reports to be drawn up for the management waqf is an accounting system. Accounting system is not only to report waqf but also includes the organizational structure of the management waqf. This study tried to explore how the management system of waqf and accounting responsibility on waqf. The purpose of this study is to give a model for accounting system of waqf. The benefits of this research is create the accounting system model that used as the basis for apply the rules of law. This model can used by regulatory agencies to set up regulations for the management of waqf property and could eventually be used by other regulatory agencies (eg, taxes) to apply the rules to manage waqf property. Abstrak Kebutuhan pertanggungjawaban nazhir atas harta wakaf menjadi pertanyaan yang penting untuk dimunculkan. Nazhir sebagai badan pengelola wakaf memiliki tanggung jawab atas pengelolaan harta wakaf. Namun, di Indonesia payung hukum dan ekonomi tentang pertanggungjawaban harta wakaf masih menjadi bahan perdebatan. Penelitian ini berusaha mengeksplorasi bagaimana sistem pengelolaan harta wakaf dan pertanggungjawaban akuntansi atas harta wakaf. Tujuan dari penelitian ini adalah memberi model sistem pertanggungjawaban akuntansi atas pengelolaan harta wakaf. Manfaat dari penelitian ini dengan terbentuknya model sistem pertanggungjawaban akuntansi dapat digunakan sebagai dasar penerapan aturan perundang-undangan. Model ini dapat digunakan oleh badan regulasi untuk membentuk peraturan-peraturan tentang pengelolaan pertanggungjawaban harta wakaf dan pada akhirnya dapat digunakan oleh badan regulasi lain (misal: pajak) untuk menerapkan aturannya dalam pengelolaan harta wakaf.